Optimisation to improve consistency in the tkatchev on high bar - Hiley, M. J.; Predescu, G. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
The purpose of this study was to improve the consistency of performance of the Tkatchev release and re-grasp on high bar. A simulation model (Hiley & Yeadon, 2003) was used to optimise the technique in the giant circle leading up to release in order to maximise the size of the window within which the gymnast could release and successfully re-grasp the bar. The optimal simulation resulted in a release window considerably larger (93 ms) than the gymnast`s actual performances (mean 29 ms). However, when the technique was required to be robust to small errors in timing the size of the release window was smaller. Performing the final hip and shoulder flexion and extension actions earlier and over a larger angle range than in the actual performances lead to the increase in size of release window.